Electrical, thermal, and structural studies on highly conducting additive-free biopolymer electrolytes for electric double-layer capacitor application - Tan, H.W.; Ramesh, Subramaniam; Liew, Chiam Wen (Springer Verlag (Germany), 2019)
Biopolymer electrolytes consisting of poly(vinyl alcohol) (PVA) and lithium trifluoromethanesulfonate (LiTf) were prepared by solution casting technique. The ionic conductivity of polymer electrolyte is increased about seven orders of magnitude which is from 3.53 ± 0.01 × 10−10 to 2.87 ± 0.01 × 10−3 S cm−1 at ambient temperature with the addition of 40 wt% of LiTf. All the polymer electrolytes follow Vogel–Tamman–Fulcher (VTF) relationship which is associated with free volume theory. The complexation between PVA and LiTf salt is proven by Fourier transform infrared spectroscopy (FTIR) study. The glass transition temperature (Tg) of polymer electrolyte was decreased with the addition of LiTf as shown in differential scanning calorimetry (DSC) thermogram. The potential difference of the polymer electrolyte showed wider range, up to 4.6 V, as proven in linear sweep voltammetry (LSV) study. Electric double-layer capacitor (EDLC) cell was assembled using prepared polymer electrolytes and two identical activated carbon-based electrodes and its electrochemical properties were also investigated. The specific capacitance of 0.37 F g−1 was obtained for the EDLC with the most conducting polymer electrolyte. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.